Bi-estabilidade óptica & condensação de Bose-Einstein de polaritons - Eduardo Adriano Cotta (2008)
Optical bistability e®ects (OB) are intrinsically related to the gain media non-linearities. In microcavities, this behavior is due to Kerr effect proportionate by polariton number, generated resonantly in strong -coupling regime, instead of the photon number. The sample was held in a cold-finger cryostat at a temperature of 10K and is constituted bytwo DBR mirrors (Al As / Al 0.2Ga 0.8 As) separated by a space fill (Al 0.3 Ga 0.7 As) containing a GaAs single quantum well of 100ºA as a gain media. Our experimental results indicate a crossing in the OB curves (with a single or double crossings) in a given excitation conditions. We present a quantitative model which is described this behavior, where is identified a competition between the Kerr (proportionate by the high polariton population) and thermal effects (proportionate by the excitation process). In order, this fact occurs due to the changes in the refractive index with opposite signal in each case. Unstable regions were experimentally registered although of cavity spontaneous oscillations (self-oscillations), same when excited in continuous mode "cw". These oscillations present different waveforms, indicating a chaos transition. In a periodic regime, the period average is cavity detuning dependent, and have approximately 80¹s. We present a model basing in the experimental results, indicating the coexistence of a laser state and a condensate state of polaritons, in which the first would be under self-phase modulation effect. Thus, the self-oscillations would be the result of the superposition of these states, leading an interference pattern of the total field emitted by the cavity. This would indicate the existence of a polariton condensate in the microcavity. These two non-linear phenomena (the crossings of the OB curves and the self-oscillations), discussed in this work, were observed for the first time by our group, showing the complexity dynamics of the trapped polaritons and a novel way to characterize the formation of condensate states in microcavities.